This study investigated the predictive relationship between test-taking anxiety, self-assessment, and students’ performance in mathematics among senior secondary school students in Uyo Education Zone of Akwa Ibom State, Nigeria. The study adopted a correlational research design. The population comprised 7,920 Senior Secondary School Two (SSS2) students in 78 public co educational secondary schools within the study area during the 2023/2024 academic session. A sample of 271 students (118 males and 153 females) was selected using a multistage random sampling technique. Three instruments were used for data collection: the Test Anxiety Inventory (TAI), the Self-assessment Questionnaire (SAQ) developed by the researcher, and the Mathematics Achievement Test (MAT) developed by the researchers, Content and face validity were established. TAI and FASQ has Cronbach Alpha reliability of 0.80 and 0.83, respectively while MAT has Kuder-Richardson (KR-20) index of 0.85 indicating high internal cons - Solomon Ahima Heman (INTERNATIONAL JOURNAL OF SOCIAL SCIENCES AND MANAGEMENT RESEARCH, 2026)
This paper investigates the evolving dynamics of terrorism and its implications on global security in the 21st century. Against the backdrop of rising transnational terrorist networks, rapid technological advancements, and shifting geopolitical landscapes, terrorism has emerged as a more complex and adaptive threat. Anchored in Rational Choice Theory, the study examines how terrorist groups strategically leverage asymmetric warfare, digital platforms for recruitment and propaganda, and the decentralization of operations to achieve their objectives. Utilizing documentary analysis and a review of secondary literature, the paper evaluates the effectiveness of existing counterterrorism strategies. Findings reveal that while military operations and intelligence-sharing have had measurable impacts, they remain insufficient without addressing the underlying socio-political drivers of radicalization. The study advocates for a multi-faceted approach to counterterrorism, one that combines international cooperation, conflict prevention, community-based resilience programs, and robust cybersecurity measures. Such comprehensive strategies are essential for mitigating the adaptive threats posed by modern terrorism and ensuring long-term global security.